Implementasi Kriptografi Dengan Menggunakan Algoritma 3Des dan Algoritma RC4 Serta Kompresi Huffman Untuk Keamanan File - Ikhsan Rahdiana; Jeremy Jonathan (Jurnal Ticom: Technology of Information and Communication, 2022)
Abstract — Problems that occur with the development of technology allow the occurrence of data theft in the company PT. Timas Suplindo, in the form of important data such as tender proposals, financial transactions and design designs for projects addressed to clients that should not be known by unauthorized parties. So it is necessary to apply cryptography at the time of sending data files to maintain the confidentiality of the information data. By using a cryptographic algorithm that is applied to the encryption and decryption process, it uses the 3DES algorithm, the RC4 algorithm and the Huffman compression method. And made with a simple and easy to use interface. The results achieved in this study are an implementation that will facilitate the sending of files in the form of .docx and .pdf in a confidential manner that is not easily known by unauthorized persons, so that the files are kept confidential.. KeyWords — Cryptography, 3DES Algorithm, RC4 Algorithm, Huffman Compression.